Controlled atmosphere storage to reduce microflora and aflatoxin production in maize - Sinaga, Siti Morin; Illangantileke, Sarath G.; Jindal, Vinod Kumar; Gupta, Chandra P.; Project Implementation Unit Asian Development Bank (PIU-ADB) (Bangkok : Asian Institute of Technology, 1986)
Microflora growth and production of aflatoxin on stored maize is a serious problem for maize producing countries and farm storage systems. Determination of the effect of modified atmosphere storage on maize was made under the modified atmosphere conditions of air, carbon dioxide and nitrogen. Aspergillus flavus, Aspergillus higher as well as penicillium species were found to be predominant fungi that are seen in high temperature, high grain moisture content storage. The carbon dioxide and nitrogen storage were found to be effective in limiting initial growth of microflora and reducing the number of colonies during storage. No aflatoxin was found in both carbon dioxide and nitrogen storage while air storage had an increased aflatoxin content with increased storage duration. The germinability of the maize was also found to be lower under air storage than in gas storage.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1986
Keywords: Corn -- Storage